Alcohol screening among young people: a prospective study from the Swiss Sentinel Surveillance System (Sentinella) of physicians' a priori opinions. (22nd February 2017) - Wenger-Bonny, Coralie; N'goran, Adjua Alexandra; Pasquier, Jérôme; Dvorak, Charles; Haller, Dagmar M; Herzig, Lilli
Abstract: Background: Systematic screening for excessive alcohol use among young people is recommended but rarely implemented. Family practitioners tend to select patients for screening, based on their preliminary subjective opinions, which may be biased. Objective: To evaluate the ability of family practitioners to identify excessive alcohol use among young people prior to screening them. Methods: This prospective study was conducted through Sentinella, an epidemiological network involving 150 family practitioners across Switzerland. All patients aged 10–24 years old, consulting participating physicians between January 1 and December 31, 2014 were eligible. First, physicians were asked to give their a priori opinion about patients' potential alcohol use. Subsequently, they asked two screening questions: (i) 'Do you drink alcohol?' and (ii) 'How many times have you had 5 (4 for girls) or more standard drinks in one day over the past year?'. Excessive alcohol use was defined as ≥1 episode of binge drinking a month. Physicians' a priori opinions were regarded as a screening test and were compared with patients' answers. Results: 7723 patients were eligible for analysis. Their mean age (SD) was 17.3(4.0) years. The two screening questions identified 3559 (46.1%) and 509 (6.6%) patients who consumed alcohol occasionally and regularly, respectively. 406 patients (5.3%) reported excessive alcohol use. Physicians' a priori opinions had a sensitivity of 26.4% and a positive predictive value of 35.5% for the identification of excessive alcohol use. Conclusion: The systematic use of a screening tool should be preferred over family practitioners' subjective opinions to identify excessive alcohol use in young people.